First record of the Asian ambrosia beetle, Xylosandrus crassiusculus (Motschulsky) (Coleoptera: Curculionidae, Scolytinae), in Slovenia - Kavčič, Andreja (Zootaxa, 2018)
Xylosandrus crassiusculus (Coleoptera: Curculionidae, Scolytinae), with the common name the Asian ambrosia beetle or the granulate ambrosia beetle, originates in tropical and subtropical regions of eastern Asia. It is one of the most widespread wood-boring beetles and among these one of the most successful invaders (IPPC 2017). Outside its native habitat, the species is present in Africa (Wood & Bright 1992, Atkinson et al. 2000), in Australia (IPPC 2017), on the Pacific Islands (Beaver 1976), in the Americas (Atkinson 1988, Rabaglia et al. 2006, Flechtmann & Atkinson 2016, Landi et al. 2017) and in Europe (Pennacchio et al. 2003, Nageleisen et al. 2015, Gallego et al. 2016, Francardi et al. 2017).